The European Union, China and Central Asia global and regional cooperation ina new era - Bossuyt, Fabienne; Dessein, Bart 1965- (Rethinking Asia and international relations, 2022)
This book examines the involvement of the European Union (EU) and China in Central Asia and critically assesses the implications this has for the region as a whole. The volume adopts a comprehensive, interdisciplinary approach, combining insights from International Relations, EU Studies, International Economics, International Law, Sinology, and History. It concentrates on three thematic levels: (1) historical and contextual, (2) geopolitical and geo-economic, and (3) socio-cultural and institutional. Paying particular attention to the role of the EU and the factors driving the EU’s and China’s relations with Central Asia, it looks at how the Central Asian countries position themselves vis-à-vis China’s growing influence, and how the balance of power between China, Russia and the EU plays out. Contributors also explore the important historical context of the ‘Silk Routes’, as well as of the erstwhile connection of the Central Asian states with the Soviet Union. Critically analyzing the potential areas for collaboration and synergy between the EU and China, the book also discusses the extent to which they share a common ground in Central Asia that could serve as a basis for long-term cooperation.It will be of interest to all scholars and students of International Relations, Economics, Sinology, and History